Intelligent energy efficient lighting using light emitting diodes - Yeong, Terence Kai Mun. (2012)
Light emitting diode (LED) technology is now an indispensible part of our lives, having a presence in almost all home applicances. LEDs come in various shapes, sizes, colours and power output, enabling them to be used almost anywhere. In light of the global energy saving trend, there is heavy research and development in the area of LED lighting, with the hope that LEDs will eventually replace the ubiquitous fluorescent light tube.